THE PROFILE OF SCHOOL LITERACY MOVEMENT AS AN EFFORT TO INCREASE READING MOTIVATION FOR PRIMARY SCHOOL STUDENTS IN KABUPATEN BONE - Irma; Sitti Aida Aziz; Sulfasyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to describe the implementation of the School Literacy Movement (SLM) program to increase students’ reading motivation at elementary schools in cluster 1 of Kecamatan Tanete Riattang Barat, Kabupaten Bone. This study also aimed to reveal supporting and inhibiting factors in implementing the SLM as well as the strategies developed by schools to overcome these inhibiting factors. This qualitative descriptive study utilized observations, interviews, and documentation to collect the data. The instruments of this study were observation sheets and interview guidelines. The subjects of this study were 15 respondents consisting of the principal, teachers, and grade VI and III students. The results showed that the school implemented the SLM program through habituation, development, and classroom learning activities. This program included the provision of facilities and infrastructure such as libraries, reading corners, reading gardens, wall magazines, posters, and slogans. In addition, the SLM program was supported by the school committee, extra-curricular activities, and the allocation of school funding. Meanwhile, the inhibiting factors included students’ lack of understanding about the implementation of the SLM, the imbalance between library capacity and the number of students, insufficient book collections, and limited time available for reading activities. Thus, strategies to overcome these factors were providing students with an understanding of the SLM, expanding the reading garden, updating the library book collection, and maximizing the use of must-read hours.